Active Detoxification in the Treatment of Abdominal Sepsis - O. M. Shevtsova; N. V. Shapovalova; T. N. Sviridova; Yu. V. Struk (Общая реаниматология, 2009)
Objective: to evaluate the efficiency of extracorporeal detoxification techniques in patients with abdominal sepsis. Subjects and methods. Three hundred and seventy-nine patients with acute generalized peritonitis were examined. Extracorporeal detoxifying techniques were used during conventional therapy in Group 1 (n=319); the other patients received only traditional therapy (a control group). The time course of changes in the parameters of toxemia, a hemostasiogram, and an immunogram were examined. Results. The study indicated significantly reduced endotoxemia and better blood aggregation resulting from the use of plasmapheresis, cryoplasmasorption, and plasmasorption, as well as stimulated immunity when the above techniques were combined with autoblood photomodification and extracorporeal immunopharmacotherapy in patients with abdominal sepsis. In severe abdominal sepsis and infectious-toxic shock, there was regression of multiple organ dysfunction and lower mortality when venovenous hemofiltration was applied. Conclusion. A differential approach to using active detoxifying techniques is needed, by taking into account the severity of the disease. Key words: abdominal sepsis, detoxifying techniques.